Theoretical and legal foundations of law enforcement collaboration in combating economic crime in Europe - Федоров, Валентин Андрійович; Федоров, В. А.; Fedorov, Valentyn A.; Антошина, Ірина Володимирівна; Антошина, I. В.; Antoshyna, Iryna V.; Бірюков, Руслан Миколайович; Бірюков, Р. М.; Biriukov, Ruslan M. (Riga : Baltija Publishing, 2025)
The subject of this study is the legal and theoretical foundations of law enforcement co-operation in Europe in combatting economic crime, with a particular focus on the co-operation of these bodies with the relevant Ukrainian authorities. The research examines legal systems across various regions of the world, with a focus on the obstacles that hinder effective collaboration. This emphasises the necessity for consistent methodologies in addressing the challenges posed by economic crime. The primary objective of the study is to establish a framework for law enforcement agencies in Europe to collaborate in the fight against economic crime. The focal point of this study is the interaction between Ukraine and the EU, with particular emphasis on Ukraine's growing integration into European political, economic, and cultural frameworks. The objective of the present article is to ascertain the fundamental concepts, legal instruments and challenges, and subsequently to propose solutions for the enhancement of collaboration. This is particularly important given that Ukraine wants to join the European Union and must address issues such as corruption within its own borders. Methodology. The article uses a combination of general scientific methods and specific legal approaches. It primarily examines how international and European Union legislation, including Council of Europe conventions and EU directives, compares with state laws. It provides a systematic analysis of the roles of Europol, Interpol, Eurojust and other institutional structures. The study also examines data from reports by foreign organisations and case studies of collaborative investigations, as well as reviewing Ukraine's law enforcement changes through case studies. This ensures that both the theoretical and practical aspects of collaboration are examined in depth. The findings demonstrate that people can work together more easily when solid legislative frameworks are in place, such as EU directives and Council of Europe treaties, as well as institutional mechanisms like SIENA and joint investigative teams. However, difficulties arise in relation to legislation, business practices and technology, particularly when it comes to tackling cybercrime. Ukraine must comply with EU regulations and collaborate more closely with Europol and Eurojust. This is crucial. Ideas for tackling economic crime in Europe include harmonising legislation, investing in technology and empowering Ukraine's anti-corruption authorities.
Fedorov V. Theoretical and legal foundations of law enforcement collaboration in combating economic crime in Europe / V. Fedorov, I. Antoshyna, R. Biriukov // Baltic Journal of Economic Studies. – Riga : Baltija Publishing, 2025. - Vol. 11(4). - Р. 177-185. URL: https://doi.org/10.30525/2256-0742/2025-11-4-177-185
Keywords: international economic security; state economic security; Interpol; Europol; economic crime; crime prevention; international co-operation in the prevention and combatting crime